The impact of nurses' sense of security on turnover intention during the normalization of COVID-19 epidemic: The mediating role of work engagement - Tang, Yao; Dias Martins, Luís M.; Wang, Shi-bin; He, Qing-xia; Huang, Hui-gen (Frontiers in Public Health, 2022)
Background COVID-19 pandemic has entered a normal stage in China. During this phase, nurses have an increased workload and mental health issues that threaten the sense of security. Poor sense of security may have a considerable impact on turnover intention through low work engagement. It was challenging to maintain the nurse workforce. Fewer studies have been conducted on the effect of nurses' sense of security on their turnover intention in that phase. This study aimed to investigate the interrelationship between nurses' sense of security, work engagement, and turnover intention during the normalization phase of the epidemic in China and to explore the impact of sense of security on turnover intention. Methods A cross-sectional survey was conducted from September 2020 to May 2021 in Guangdong Province, China. Data were collected online using Sense of Security Scale for Medical Staff (SSS-MS), Utrecht Work Engagement Scale (UWES), and Turnover Intention Scale. Pearson's correlation analysis was used to assess the correlation between sense of security, work engagement, and turnover intention. The hypothesis model used multiple linear regression models and the bootstrapping procedure to analyze the relationship between these variables. Results Data were collected from 2,480 nurses who met the inclusion criteria. Over half(64.5%) of nurses had a high and very high turnover intention. After controlling the demographic and working variables, sense of security (β = 0.291, P < 0.001) had a direct positive effect on work engagement. Sense of security (β = −0.447, P < 0.001) and work engagement (β = −0.484, P < 0.001) had a direct negative effect on turnover intention. Sense of security and all of its components were associated with turnover intention through the partially mediating effects of work engagement. Conclusions Nurses' turnover intention was at a high level during the normalization phase of the epidemic. Sense of security and its components act as positive resources to reduce turnover intention by improving work engagement. Policy makers and managers may pay attention to the needs of nurses' sense of security, which may be a new perspective to help managers reduce their turnover intention and stabilize the nurse team.